Moisture gradient on the agronomic performance of rye cropped in arid land environment - García-Hernández, José Luis; Sosa-Yañez, Lorena Carolina; López-Ahumada, Guadalupe Amanda (Ecosistemas y Recursos Agropecuarios, 2024)
In areas with arid and semi-arid climates, the availability and quality of water are critical factors for the development of agronomy. To face the challenge, an alternative for the use of this resource is the implementation of efficient and sustainable techniques such as the use of drip irrigation. The objective of the work was to analyze the agronomic behavior of rye under unfavorable water and temperature conditions to determine the effectiveness of phenotypic stability on La Costa de Hermosillo, Sonora, Mexico. Two rye genotypes were planted under a split plot experimental design (large plot: three water levels and small plot: two genotypes of seeds obtained in different cycles). The agronomic characteristics of the plant, the physicochemical characteristics of the grain were evaluated; and the significance between the different variables was determined with a correlation analysis. The analysis of variance revealed effects on plant height, number of spikes and grains, grain size, thousand grain weight, yield and protein content of rye due to the different water regimes used. Between 219-314 spikes per linear meter were obtained, with a commercially acceptable grain size (7.45-7.95 mm long x 2.18-2.40 mm wide). High yield values (1.72-3.11 t ha-1) were also observed, as well as excellent protein content (20.3-22.8%). These results demonstrate that rye is a versatile cereal that adapts to adverse environmental conditions such as a decrease in the amount of irrigation water and extremely high temperatures.
Keywords: Irrigation water, extreme heat, protein content, adaptation crop, abiotic stress.